IMPLEMENTATION OF HEALTH TECHNOLOGY ASSESSMENT WORK IN A HOSPITAL IN KAZAKHSTAN. (9th March 2016) - Kosherbayeva, Lyazzat; Hailey, David; Kurakbaev, Kural; Tsoy, Aleksey; Zhuzzhanov, Ormanbek; Donbay, Abilay; Kumar, Ainur; Nadyrov, Kamalzhan
Abstract : Objectives: The aim of this study was to implement health technology assessment (HA) in the First General City Hospital in Astana, Kazakhstan. Methods: We organized trainings to familiarize hospital staff with the purpose and details of HTA. An HTA committee was established, with representation from hospital physicians and managers, and criteria for prioritization of health technologies determined. Clinical departments of the hospital were asked to prepare applications for new technologies for their services. Results: The HTA committee reviewed five applications and selected a technology from one of these, on single incision laparoscopic surgery (SILS), for assessment. A short HTA report on SILS was prepared, covering its safety, clinical effectiveness, and cost effectiveness. The report was used to support a request to the Department of Health for additional funding to implement this technology within the hospital. This funding was approved and SILS was established in several hospital departments. Conclusions: This successful initial experience with HTA has paved the way for its routine use by the hospital for informing decisions on the procurement and use of new health technologies.